A highly sensitive electrochemical microRNA-21 biosensor based on intercalating methylene blue signal amplification and a highly dispersed gold nanoparticles/graphene/polypyrrole composite. Issue 8 (9th March 2021) - Pothipor, Chammari; Aroonyadet, Noppadol; Bamrungsap, Suwussa; Jakmunee, Jaroon; Ounnunkad, Kontad
Abstract : An ultrasensitive electrochemical biosensor based on a gold nanoparticles/graphene/polypyrrole composite modified electrode and a signal amplification strategy employing methylene blue is developed as a potential tool for the detection of miRNA-21. Abstract : Numerous clinical studies suggest that microRNAs (miRNAs) are indicative biomolecules for the early diagnosis of cancer. This work aims to develop a cost-effective and label-free electrochemical biosensor to detect miRNA-21, a biomarker of breast cancer. An electrochemical sensor is fabricated using a nanocomposite, consisting of graphene (GP), polypyrrole (PPY) and gold nanoparticles (AuNPs), modified onto a screen-printed carbon electrode (SPCE) to improve electron transfer properties and increase the degree of methylene blue (MB) intercalation for signal amplification. The GP/PPY-modified electrode offers good electrochemical reactivity and high dispersibility of AuNPs, resulting in excellent sensor performance. Peak current of the MB redox process, which is proportional to miRNA-21 concentration on the electrode surface, is monitored by differential pulse voltammetry (DPV). Under optimal conditions, this sensor is operated by monitoring the MB signal response due to the amount of hybridization products between miRNA-21 target molecules and DNA-21 probes immobilized on the electrode. The proposed biosensor reveals a linear range from 1.0 fM to 1.0 nM with a low detection limit of 0.020 fM. In addition, the miRNA-21 biosensor provides good selectivity, high stability, and satisfactory reproducibility, which shows promising potential in clinical research and diagnostic applications.